2023
DOI: 10.3389/fcimb.2023.1141474
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between caries activity and salivary microbiota in preschool children

Abstract: Early childhood caries (ECC) is the most common chronic infectious oral disease in preschool children worldwide. It is closely related to the caries activity (CA) of children. However, the distribution characteristics of oral saliva microbiomes in children with different CA are largely underexplored. The aim of this study was to investigate the microbial community in saliva of preschool children with different CA and caries status, and to analyze the difference of microbial community in saliva of children with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 65 publications
1
3
0
Order By: Relevance
“…In our study ,there were no statistical differences in alpha diversity observed between males and females across data sets using standard estimates, including standard Shannon entropy and Chao1 diversity approaches, which has been reported in other studies, including a study conducted in the neighbouring country of Qatar [ 23 , 24 ]. However, the high versus low dental caries groups had statistically significant differences in alpha diversity using the same approaches.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…In our study ,there were no statistical differences in alpha diversity observed between males and females across data sets using standard estimates, including standard Shannon entropy and Chao1 diversity approaches, which has been reported in other studies, including a study conducted in the neighbouring country of Qatar [ 23 , 24 ]. However, the high versus low dental caries groups had statistically significant differences in alpha diversity using the same approaches.…”
Section: Discussionsupporting
confidence: 76%
“…The Selenomonadaceae family observation is consistent with an over-representation of a severe caries cohort in a 2020 Indian study conducted by Kalpana et al [ 32 ]. In addition a report by Lin et al identified the Selenomonadaceae family to be a potential biomarker for high dental caries subjects and exhibited a positive correlation with DMFT [ 24 ]. Moreover, Tang et al showed that the anaerobic glycolytic pathway was significantly upregulated in the high dental caries group in unison with upregulation of these bacterial families, which leads to elevated acid production, thereby overwhelming the healthy microbiome capacity for buffering [ 14 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with the current study, Pratyusha et al [ 22 ] conducted a comparative cross-sectional study on association of serum VD and salivary Ca level in 3-11-year-old schoolchildren with dental caries, indicating that VD deficiency and lower salivary Ca levels may be the potential risk factors for the occurrence of dental caries. The composition of salivary microbial community was highly correlated with Ca, and the cariogenic microorganisms present in the oral cavity play a key role in the occurrence and development of childhood caries, and the formed biofilm can metabolize carbohydrates to produce organic acids, resulting in local pH decline and demineralization of dental hard tissues [ 23 ]. Differently, in this study, we assessed the dietary Ca intake level, which may have specific underlying mechanisms to explain the relationship of deficient dietary Ca intake and high odds of dental caries.…”
Section: Discussionmentioning
confidence: 99%
“…In 2019, the National Health Commission of China implemented the Healthy Mouth Action Program (2019–2025) to increase oral health awareness and promote oral health–enhancing behavior in the public. Preventing and treating dental caries have long been a subject of social research, and many studies have focused on children[ 14 ]. In 2021, the National Health Commission implemented the Action Plan for Improvement of Maternal and Infant Safety (2021–2025)[ 15 ], which emphasizes hygiene and maternal and infant safety.…”
Section: Discussionmentioning
confidence: 99%